The Prevalence of Enteric Viruses in Bivalve Molluscs in a Farming Area in Liguria, Northwest Italy - Chiara Masotti; Laura Serracca; Erica Costa; Barbara Betti; Aitor Garcia-Vozmediano; Elisabetta Suffredini; Roberta Battistini (Pathogens)
Bivalve molluscs are filter-feeding organisms, capable of concentrating pathogenic microorganisms from the surrounding environment, thus contributing to the spread of viral pathogens, which they can transmit to humans, especially if eaten raw or undercooked. Although norovirus (NoV) and the hepatitis A virus (HAV) are considered the most common causes of foodborne infections, in recent years, other viruses with a zoonotic potential have been identified in shellfish, such as the hepatitis E virus (HEV), astrovirus (AsV), and aichi virus (AiV). The aim of the study was to investigate the presence of classical and emerging pathogenic enteric viruses in oysters (Crassostrea gigas) and mussels (Mytilus galloprovincialis) from a mollusc farming area in the northwest of Italy, between April 2022 and March 2023. In the period considered, a total of 168 samples (84 oysters and 84 mussels) were analysed. The prevalence of NoV was highest, with 32.7% (55/168) positive samples, followed by 18.4% (31/168) for AsV and 19.6% (33/168) for AiV. This study revealed, for the first time, the presence of AsV and AiV in molluscs farmed in this sea area. All the samples tested were negative for HAV and HEV. The emergence of new enteric viruses like AiV and AsV in bivalve molluscs underscores the importance of improving surveillance and environmental monitoring methods, particularly in shellfish production areas.